Consensus and activism through collective exchanges: a focus on El Cambalache, Mexico. Issue 11 (10th October 2016) - Araujo, Erin
Abstract : Purpose: The purpose of this paper is to explore how consensus decision making serves as a foundation for organizing an alternative economy while the agency of the economic project itself organizes participants because it serves to distribute resources as people need them and foment a community of sharing based on the concept that as individuals we are lacking but as a community we have enough. The paper asserts that as activists looking to foment change, alternative economic projects in themselves are actors in organizing community building and resistance to capitalism. Design/methodology/approach: El Cambalache (The Swap in English), located in San Cristobal de las Casas, Chiapas, Mexico, is an exchange-based money-less economy that trades unwanted items as well as knowledge, abilities and skills that one wants to share. The project receives anything; specifically used, broken and/or unwanted electronics as well as just about anything else that one might possess. In exchange people provide laptop maintenance classes, language exchange, land to be worked, rooms, gardening services, objects, stories, etc. The rules in this money-less non-capitalist economy organize participation through one exchange or many. Findings: Consensus decision making is an effective method for engaging in non-hierarchical research projects. Originality/value: This project contributes to research in heterodox economies by presenting an original project with a new suggestion for exchange value as an inclusive process of exchange among participants in the economy. It also provides evidence that consensus decision making can be a useful and productive method for research.